Dimeric Drug Polymeric Micelles with Acid‐Active Tumor Targeting and FRET‐Traceable Drug Release. Issue 3 (6th December 2017) - Guo, Xing; Wang, Lin; Duval, Kayla; Fan, Jing; Zhou, Shaobing; Chen, Zi
Abstract: Trans‐activating transcriptional activator (TAT), a cell‐penetrating peptide, is extensively used for facilitating cellular uptake and nuclear targeting of drug delivery systems. However, the positively charged TAT peptide strongly interacts with serum components and undergoes substantial phagocytosis by the reticuloendothelial system, causing a short blood circulation in vivo. In this work, an acid‐active tumor targeting nanoplatform DA‐TAT‐PECL is developed to inhibit the nonspecific interactions of TAT in the bloodstream. 2, 3‐dimethylmaleic anhydride (DA) is used to convert the TAT's amines to carboxylic acid; the resulting DA‐TAT is conjugated to poly(ethylene glycol)‐poly(ε‐caprolactone) (PEG‐PCL, PECL) to get DA‐TAT‐PECL. After self‐assembly into polymeric micelles, they are capable of circulating in the physiological condition for a long time and promoting cell penetration upon accumulation at the tumor site and deshielding the DA group. Moreover, camptothecin (CPT) is used as the anticancer drug and modified into a dimer (CPT)2 ‐ss‐Mal, in which two CPT molecules are connected by a reduction‐labile maleimide thioether bond. The Förster resonance energy transfer signal between CPT and maleimide thioether bond is monitored to visualize the drug release process, and effective targeted delivery of antitumor drugs is demonstrated. This pH/reduction dual‐responsive micelle system provides a new platform for high fidelity cancer therapy. Abstract : A dimeric drug polymeric micelle with acid‐active tumor targeting and Förster resonance energy transfer (FRET)‐traceable drug release is successfully fabricated. It has unique features such as long blood circulation through shielding of the cationic charges of trans‐activating transcriptional activator (TAT), enhanced cellular internalization by regenerating the original TAT in acidic tumor tissue, and intracellular glutathione‐triggered FRET‐traceable drug release.